Hemoperitoneum secondary to mesenteric laceration after abdominal trauma - Case report - Marta M. Ferreira; Narcisa Guimarães; Inês Bolais Mónica; Simone Oliveira; Daniela Pais; Sara Andrade; Alice Fonseca; Ana Couceiro; Isabel Borges; José Valente Cecílio (Trauma Case Reports, 2021)
Mesenteric laceration is an uncommon cause of hemoperitoneum, with nonspecific signs and symptoms and frequently is camouflaged by the signs of other traumatic lesions. There is a high risk to go unnoticed increasing morbidity and mortality.We report a case of a 43-year-old man, who was involved in a motorcycle accident, with thoraco-abdomino-pelvic trauma, but without evidence of intra-abdominal lesions on exams, with exception of hemoperitoneum. Due to hemodynamic instability, it was performed an exploratory laparotomy. Intraoperative findings were mesenteric lacerations affecting a small bowel segment.This case demonstrates that a high index of suspicion is necessary to diagnose and treat lesions like mesenteric laceration, not visible early on imaging but potentially fatal, with high risk of complications.